The financial management of local authorities in Ghana: the case of Adentan Municipal Assembly - Tamakloe, MacCharles Yaw (2014)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Commonwealth Executive Masters of Business Administration